2000
DOI: 10.1073/pnas.110147297
|View full text |Cite
|
Sign up to set email alerts
|

Operons in Escherichia coli : Genomic analyses and predictions

Abstract: The rich knowledge of operon organization in Escherichia coli, together with the completed chromosomal sequence of this bacterium, enabled us to perform an analysis of distances between genes and of functional relationships of adjacent genes in the same operon, as opposed to adjacent genes in different transcription units. We measured and demonstrated the expected tendencies of genes within operons to have much shorter intergenic distances than genes at the borders of transcription units. A clear peak at short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
324
1
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(344 citation statements)
references
References 24 publications
16
324
1
3
Order By: Relevance
“…Although these data have all proven to be valid predictors of operon structure, it is striking that these studies have also consistently demonstrated that one of the most valuable predictors is simply intergenic distance. The distances between genes within an operon tend to be considerably shorter than the distances between genes that are not cotranscribed, and in several recently developed algorithms, intergenic distance was shown to be more informative than any other data source, including even microarray-based expression data (3,7,28,34). In addition, this trend appears to be universal in bacterial genomes, making it a very attractive option for a generalized, portable prediction algorithm (7,15,33).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although these data have all proven to be valid predictors of operon structure, it is striking that these studies have also consistently demonstrated that one of the most valuable predictors is simply intergenic distance. The distances between genes within an operon tend to be considerably shorter than the distances between genes that are not cotranscribed, and in several recently developed algorithms, intergenic distance was shown to be more informative than any other data source, including even microarray-based expression data (3,7,28,34). In addition, this trend appears to be universal in bacterial genomes, making it a very attractive option for a generalized, portable prediction algorithm (7,15,33).…”
mentioning
confidence: 99%
“…Progress has also been made toward a more generalized method for operon prediction, and a number of groups have constructed algorithms based on a variety of diverse information sources, including codon usage statistics (3,4) and the identification of promoter and terminator sequences (6,28,33,34). Although these data have all proven to be valid predictors of operon structure, it is striking that these studies have also consistently demonstrated that one of the most valuable predictors is simply intergenic distance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For the Escherichia coli genome, operon pair predictions using the intergenic distance information were 82% accurate. 1,2 An alternative method of operon prediction is based on gene expression measurements. Using cDNA microarray technology, the expression levels can be measured simultaneously for all genes in the genome by measuring the corresponding mRNA concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, many previous studies have suggested that constraints on gene expression and function have shaped the organization of genes in the genome. Due to lack of appropriate data related to the three-dimensional genomic organization, earlier studies considered the one-dimensional (linear) organization of genomes, and many of them emphasized the higher levels of genomic organization in prokaryotes compared with eukaryotes; for example, it is known that prokaryotes (unlike most eukaryotes) tend to contain operons of co-transcribed genes with related function 9 .…”
mentioning
confidence: 99%